The Effect of Changes in Land Cover and Vegetation Density on Urban Heat Island in Semarang City - Susiyowati Indah Ayuni; Arief Adhika Widyatama; Nanda Mutiara Zani (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
The urbanization process can be seen not only as influenced by increasing population growth but also the phenomenon of urbanization. The city of Semarang from 1999 to 2019 saw an increase of half a million people with a total population of around 1.81 million people. Along with population growth that occurs, land conversion to meet the needs of life often clashes with the presence of vegetated land. As a result, the area ofvegetated land slowly decreases. On the other hand, the massive build-up of this area makes it easier to reflect and absorb solar heat. As a result, the average surface temperature of the city gradually rises which causes the formation of hot spots that cause changes in climate and weather elements, thus triggering the formation of an Urban Heat Island (UHI). The increase in temperature in urban areas affects not only the comfort of cities but also the health of urban communities, which will impact various city line activities. This urban heat island study, related to changes in land use in Semarang, is urgently needed to make wiser spatial planning decisions. In line with the problems above, this study is aimed at analyzing the effect of changes in land cover and vegetation density on the area of Urban Heat Island (UHI) in Semarang City. The approach used is forecasting with multiple regression analysis methods. Sources of data used are secondary data and population data. The data used is time series data. Based on the statistical analysis results indicate that the variables of land cover and vegetation density have a significant influence on the distribution of surface temperature. The land cover component has a positive effect while the vegetation density component harms the surface temperature distribution area. The appearance of the trendline results in an increasing area of surface temperature distribution in 2030 with 3 scenarios, namely, pessimistic, moderate, and optimistic. The preparation of a planning scenario in which an optimistic scenario can be adopted by the government so that the area of high urban surface temperatures does not expand and have an impact on the level of community vulnerability to extreme weather.